1990
DOI: 10.1016/s0006-3495(90)82428-0
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation of the photosynthetic membrane

Abstract: The study examines the relationship between electric field-induced conductivity and permeability changes in a biological membrane (electroporation) and the amplitude-duration parameters of the externally applied electric field. These reversible changes were characterized in giant photosynthetic membrane vesicles by means of the calibrated response of an intrinsic voltage-sensitive optical probe (electrophotoluminescence) and by the uptake studies of dextran-FITC fluorescent probes of different molecular weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Together these results indicate that the largest pores formed during electroporation, which have a sufficient lifetime for NPs to pass, are of the order of 30 nm. This is in line with early estimations of pore sizes using large macromolecules (dextrans), for which pore sizes of close to 10 nm were obtained, [ 59–61 ] and more recent studies suggesting that transiently larger pores can be formed. [ 62 ]…”
Section: Resultssupporting
confidence: 90%
“…Together these results indicate that the largest pores formed during electroporation, which have a sufficient lifetime for NPs to pass, are of the order of 30 nm. This is in line with early estimations of pore sizes using large macromolecules (dextrans), for which pore sizes of close to 10 nm were obtained, [ 59–61 ] and more recent studies suggesting that transiently larger pores can be formed. [ 62 ]…”
Section: Resultssupporting
confidence: 90%
“…It was suggested that excessive field strength could lead to permeation of a wider area, or forming larger pores that may exceed the resealing limit (Hui, 1996). The same conclusion was also reported by Rosemberg and Korenstein (1990); E controlling the total area of membrane that undergoes permeabilization, and T the diameter of "electropores." Longer pulses corresponding to low field strength were reported to be more advantageous than the short ones in terms of transfection success (Kubiniec et al, 1988).…”
Section: Discussionmentioning
confidence: 61%
“…Several models assumed that transfer across the membrane occurred across pores, which has never been observed. Different calculations of the "electropores" diameter have been proposed, from 0.39 to 5.8 nm, that correspond to 0.01-0.1% of the membrane area (Sowers and Lieber, 1986;Kinosita et al, 1988;Rosemberg and Korenstein, 1990;Hibino et al, 1993;Neumann et al, 1996). If these values are compatible with the size of small molecules (M w Ͻ 10), they cannot support the penetration of macromolecules such as plasmid DNA and enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Electroporation is generally considered to enhance the transient formation of aqueous pores in the plasmalemma, as a result of the abnormally high electrical potential difference imposed on those parts of the membrane perpendicular to the externally applied field (Rosemberg & Korenstein 1990). More than one type of process is involved depending on the field strength, the membrane conductivity, and the pulse number, duration and polarity (Rosemberg & Korenstein 1990;Toner & Cravalho 1990). The permeation of solutes through these enlarged pores is driven by a transmembrane concentration gradient in the case of uncharged molecules such as glycerol, or by a combination of concentration and electrical gradients in the case of ions.…”
Section: Dimensions Volumementioning
confidence: 99%